2012
DOI: 10.2217/pgs.12.86
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drug Dosage and Therapeutic Response in Schizophrenia is Influenced by ABCB1 Genotypes: A Study from a South Indian Perspective

Abstract: The study suggests that a priori knowledge of ABCB1 genotypes can provide a significant input into evaluating the patient's response to medication, and minimizing redundant dosing and refractoriness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
(37 reference statements)
2
20
0
Order By: Relevance
“…Nonresponders had relatively lower expression of ABCB1 and a corresponding increased miR-27a expression when compared with the responder group. This is interesting in the background of our earlier study, where we reported that the individuals carrying risk genotypes for nonresponse in rs1045642 and rs2032582 became refractory with increased dosage [15]. In the present study, we had all the patients with ABCB1 risk alleles for nonresponse from rs1045642 and rs2032582, and all the additionally screened functionally relevant promoter and 3´UTR polymorphisms were also found to be monomorphic.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Nonresponders had relatively lower expression of ABCB1 and a corresponding increased miR-27a expression when compared with the responder group. This is interesting in the background of our earlier study, where we reported that the individuals carrying risk genotypes for nonresponse in rs1045642 and rs2032582 became refractory with increased dosage [15]. In the present study, we had all the patients with ABCB1 risk alleles for nonresponse from rs1045642 and rs2032582, and all the additionally screened functionally relevant promoter and 3´UTR polymorphisms were also found to be monomorphic.…”
Section: Discussionmentioning
confidence: 71%
“…Patients were rated using Extended Brief Psychiatric Rating Scale for symptom severity, and were classified as responders (n = 129) and nonresponders (n = 55) based on the 50% improvement in Brief Psychiatric Rating Scale rating after 1 year of antipsychotic treatment, as described earlier [15]. Schizophrenia patients taking valproic acid were excluded from the study.…”
Section: Clinical Subject Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markers rs7787082 G and rs10248420 A alleles in ABCB1 were more frequently observed in non-responders (92). A naturalistic study by Vijayan et al found that individuals with 3435CC (rs1045642) and 1236CC (rs1128503) genotypes responded better to a variety of APs, using the BPRS scale (93). Notably, earlier monotherapy studies in other populations found that individuals with the 3435TT genotype showed better response to olanzapine (94), and those with the 1236TT polymorphism showed better response to risperidone (95).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Gupta et al (2013) attempted to elucidate a genetic signature, which could predict patients' response to atypical monotherapy, and showed that 76 % patients carrying a combination of four SNPs did not show favourable response to atypical antipsychotics. A recent study evaluated the role P-glycoprotein (ABCB1) polymorphism in understanding the effectiveness of antipsychotic medications in schizophrenia and reported that patients with favourable homozygous genotypes of rs1045642 and rs2032582 display better response with increased dosage, while those carrying the risk genotype manifest refractoriness on increased dosage (Vijayan et al 2012).…”
mentioning
confidence: 99%